Heritage Tourism: The Back-and-Forth among Tourists, Sites and Residents: The Back-and-Forth among Tourists, Sites and Residents - Agbabiaka, Hafeez Idowu; Akinbinu, Akinkule Akintan; Omisore, Emmanuel Olufemi; Abiodun, Abiodun Adebola; Sodangi, Abubakar Bawa (Economic and Environmental Studies, 2020)
Heritage tourism destinations attract heterogeneous number of players each with significantly different interests at the expense of residents. Therefore, this study assesses impacts and patronage of heritage tourism sites on the host communities in Osun State, Nigeria. Data for this study was derived through questionnaire administration. Random sampling without replacement was used to select eleven (11) heritage tourism sites in which two hundred and twenty-two (222) questionnaire were administered residents. Findings revealed the propelling factors of the influx of tourist to the heritage sites are socio-economic (33.06%), service (17.75%), mobility (12.77%) and management factors (10.78%) and the possible outcomes are both positive and negative, which were further categorized into Social, economic and environmental impacts. The implications of this study revealed the prominence of social vices such as increase in prostitution, traffic congestion, and noise pollution among others in the areas accommodating the heritage tourism sites, hence appropriate policies for proper guidance among the heritage tourism sites, the tourists and the residents.